Competency-based pre-service education for clinical psychology training in low- and middle-income countries: Case study of Makerere University in Uganda - Alipanga, Benjamin; Kohrt, Brandon A. (Frontiers in Psychology, 2022)
Reducing the global treatment gap for mental health conditions in low- and middle-income countries (LMICs) requires not only an expansion of clinical psychology training but also assuring that graduates of these programs have the competency to effectively and safely deliver psychological interventions. Clinical psychology training programs in LMICs require standardized tools and guidance to evaluate competency. The World Health Organization (WHO) and UNICEF developed the “Ensuring Quality in Psychological Support” (EQUIP) platform to facilitate competency-based training in psychosocial support, psychological treatments, and foundational helping skills, with an initial focus on in-service training for non-specialists. Our goal was to design the first application of EQUIP to implement competency-based training into pre-service education for clinical psychology trainees. With Makerere University in Uganda as a case study, we outline an approach to develop, implement, and evaluate a competency-based curriculum that includes seven steps: 1) Identify core clinical psychology competencies; 2) Identify evaluation methods appropriate to each competency; 3) Determine when competency evaluations will be integrated in the curriculum, who will evaluate competency, and how results will be used; 4) Train faculty in competency-based education including conducting competency assessments and giving competency-based feedback; 5) Pilot test and evaluate the competency-based education strategy with faculty and students; 6) Modify and implement the competency-based education strategy based on pilot results; and 7) Implement ongoing evaluation of the competency-based curriculum with continuous quality improvement. This approach will be formally evaluated and establish as a foundation for pre-service training in other low-resource settings.